God, Humanity and the Cosmos: Challenging a Challenging Textbook - Drees, Willem B. (Zygon, 2018)
Christopher Southgate has been the editor of the textbook God, Humanity and the Cosmos. I consider this textbook fair on science and wise in intertwining issues in theology and science with ecology, climate change, and technology. It might also be challenging for students, as it introduces them to a variety of perspectives and a rich palette of literature. I wonder whether such a book, with its strong theological, cognitive, orientation will remain relevant in European contexts, given shifts in society away from Christianity and changes in understanding what it is to be religious.